T-DM1 with concurrent radiotherapy in HER2-positive breast cancer: preclinical evaluation and mechanisms, prediction, and exploration of adverse effects - Guangmin Wan; Lu Yang; Quan Wang; Gang Xu (Discover Oncology)
Abstract Human epidermal growth factor receptor 2 (HER-2) serves as a pivotal target for breast cancer treatment and a vital prognostic marker. Anti-HER-2 therapies, which are integral to the management of HER-2-positive breast cancer, including monoclonal antibodies (e.g., trastuzumab and pertuzumab), tyrosine kinase inhibitors (e.g., lapatinib and pyrotinib), and antibody–drug conjugates (ADCs) such as trastuzumab emtansine (T-DM1). ADCs consist of a monoclonal antibody, a linker, and a cytotoxic payload, engineered to deliver chemotherapy selectively to tumor cells, thereby reducing the systemic toxicity associated with traditional chemotherapy. T-DM1, a HER-2-targeting ADC, combines the humanized anti-HER-2 IgG1 trastuzumab with DM1, a cytotoxic agent that inhibits microtubule formation. T-DM1 has significantly enhanced the prognosis of HER-2-positive breast cancer patients who fail to achieve a pathological complete response or develop distant metastases after neoadjuvant trastuzumab and pertuzumab therapy. While the combination therapy of T-DM1 with radiotherapy demonstrates an acceptable safety profile overall, clinicians should remain vigilant regarding potential severe treatment-related toxicities that have been observed in specific clinical scenarios. Nevertheless, limited research exists regarding the adverse effects and mechanisms of T-DM1 in combination with radiotherapy. This review investigates preclinical studies on the interactions between T-DM1 and radiotherapy, investigates associated adverse effects and their underlying mechanisms, identifies predictive factors and prognostic implications, and explores potential therapeutic strategies involving the concurrent T-DM1 with radiotherapy.